Dynamics in a Lotka-Volterra Predator-Prey Model with Time-Varying Delays - Changjin Xu; Yusen Wu (Abstract and Applied Analysis)
A Lotka-Volterra predator-prey model with time-varying delays is investigated. By using the differential inequality theory, some sufficient conditions which ensure the permanence and global asymptotic stability of the system are established. The paper ends with some interesting numerical simulations that illustrate our analytical predictions.